2023
DOI: 10.3390/jcm12072581
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic Manifestations of Cardiac Amyloidosis: Challenges in Risk Stratification and Clinical Management

Abstract: Amylodiosis is a systemic disease characterized by extracellular deposits of insoluble amyloid in various tissues and organs. Cardiac amyloidosis is a frequent feature of the disease, causing a progressive, restrictive type of cardiomyopathy, and is associated with adverse clinical outcomes and increased mortality. The typical clinical presentation in patients with cardiac amyloidosis is heart failure (HF) with preserved ejection fraction. Most patients present with typical symptoms and signs of HF, such as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Since CA has gained more clinical recognition in the field of heart failure, 22 , 23 various arrhythmias ranging from brady- and tachyarrhythmias accompanying this disease have also been increasingly addressed. 5 In particular, VAs and their potential link to adverse clinical outcomes have been a matter of concern. However, identification of patients with CA who may benefit from ICD therapy remains to be a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CA has gained more clinical recognition in the field of heart failure, 22 , 23 various arrhythmias ranging from brady- and tachyarrhythmias accompanying this disease have also been increasingly addressed. 5 In particular, VAs and their potential link to adverse clinical outcomes have been a matter of concern. However, identification of patients with CA who may benefit from ICD therapy remains to be a challenge.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 There are two main forms of disease, namely light chain amyloidosis ( A L) and transthyretin amyloidosis (ATTR), both of which provide a substrate for electro-mechanical remodeling 3 , 4 and various arrhythmias. 5 Compared with patients with the ATTR subtype, those with AL-CA often develop complex ventricular arrhythmias (VA) and have a poorer prognosis. 1 , 3 It was reported that 5–27% of AL-CA patients present with a non-sustained ventricular tachycardia (NSVT), 6 , 7 and premature ventricular contractions (PVCs) were found in 72% patients.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Both acquired and common and rare genetic and risk factors exist for cardiac arrhythmias. 1 , 2 Cardiac amyloidosis is a rare disease that may manifest various arrhythmias, such as atrioventricular nodal block, atrial fibrillation, and ventricular tachyarrhythmias. 2 Amyloidosis is characterized by extracellular deposits of amyloid in various organs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Cardiac amyloidosis is a rare disease that may manifest various arrhythmias, such as atrioventricular nodal block, atrial fibrillation, and ventricular tachyarrhythmias. 2 Amyloidosis is characterized by extracellular deposits of amyloid in various organs. 2 Cardiac amyloidosis with cardiomyopathy is a frequent feature of amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation